2003
DOI: 10.1002/cne.10754
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptor structural specialization in canine and rodent testicular “free” nerve endings

Abstract: The receptive fields (RFs) of polymodal nociceptor units of canine testis consist of small fascicles of branching axons ending as clusters within the thin vascular layer overlying the seminiferous tubules. This propitious arrangement enabled serial reconstruction of electron micrographs of a flat, punctate zone, identified during recording of impulse discharge of a single physiologically characterized nociceptor "unit." The RFs showed multiple axons, with some branching and sequential vesicle-containing swelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…It should be noted that the morphological qualities of both the central column free nerve endings and peripheral free nerve endings correspond well to those reported for the varicose (beaded) and fine (plain) free nerve endings, respectively, in human digital skin (Cauna, 1980). However, the peripheral terminals in this system appear to lack a distinct axonal reticulum and dense aggregations of microvesicles and appear to differ somewhat from the canine and rodent testicular free nerve endings described by Kruger et al (2003a), though without serial sectioning the length of the terminals, the presence of these structures cannot be ruled out.…”
Section: Structure Of Peripheral Free Nerve Endings and Nature Of Thesupporting
confidence: 82%
“…It should be noted that the morphological qualities of both the central column free nerve endings and peripheral free nerve endings correspond well to those reported for the varicose (beaded) and fine (plain) free nerve endings, respectively, in human digital skin (Cauna, 1980). However, the peripheral terminals in this system appear to lack a distinct axonal reticulum and dense aggregations of microvesicles and appear to differ somewhat from the canine and rodent testicular free nerve endings described by Kruger et al (2003a), though without serial sectioning the length of the terminals, the presence of these structures cannot be ruled out.…”
Section: Structure Of Peripheral Free Nerve Endings and Nature Of Thesupporting
confidence: 82%
“…We speculate that branch points are exposed to distortion during strong contractions or distension of the intestine. Branching nociceptor axons with regular swellings in extensive terminal fields are found on vascular structures in testis26, where ultrastructural specialisations have been detailed, comparable to nociceptor terminals in the knee joint, pleura and dura mater27. Whether the mesenteric mechanosensitive axonal structures identified here actually constitute “nerve endings” and share similar ultrastructural characteristics remains to be determined.…”
Section: Discussionmentioning
confidence: 74%
“…These measurements were performed in isolated cell bodies of DRG neurons, where the ER is clearly present. It has also been shown that the nerve terminals of free nerve endings in the skin contain axonal reticulum, the equivalent of the ER, making it possible that store operated Ca 2+ channels function not only in the cell bodies, but also at the nerve terminals (Kruger et al, 2003). Interestingly, heat over 35 C° has been shown to induce clustering of STIM1 and activation of store operated Ca 2+ entry (Xiao et al, 2011).…”
Section: Ion Channels Primarily Activated By Plc Signalingmentioning
confidence: 99%